Constructing guilt: The trial of Leopoldo López - Alvarez, Alexandra (Language and Law / Linguagem e Direito, 2017)
Leopoldo López is a prisoner of conscience. The prosecution, relying on two forensic linguists’ expert reports, claimed that the politician’s discourse was the direct cause of the violence on February 12, 2014 in Caracas. I analyzed the Condemnatory Sentence issued by the prosecution following Shuy’s “Inverted Pyramid” heuristic (2013; 2014). I found opposing agendas and schemas as well as confIicting representations of speech acts. Linguistic analysis of his allegedly criminal speeches also demonstrates a wide divergence between the ways they are perceived by the prosecution and defense. Lopez’s discourse indicates that he considered these speech events as political discourse (Chilton, 2004); examination of the language he actually used does not support the government’s accusation that Lopez was encouraging public violence.